The variation of the leakage current characteristics of W/Ta2O5/W MIM capacitors with the thickness of the bottom W electrode. (June 2016) - Yu, D.Q.; Lau, W.S.; Wong, Hei; Feng, Xuan; Dong, Shurong; Pey, K.L.
Abstract: In this paper, we will report that the leakage current characteristics can be a function of the bottom electrode. The variation of the bottom tungsten electrode thickness can affect the leakage current characteristics of W/Ta2 O5 /W MIM capacitors mainly through two mechanisms. The first mechanism is that the Ta2 O5 CVD process can be influenced by the W bottom electrode thickness. Experimentally it was observed that the thickness of the Ta2 O5 film deposited by CVD is noticeably different for samples with different bottom W electrodes with different thicknesses. The second mechanism is that the surface roughness of the bottom W electrode increases with increasing thickness, resulting in a smaller effective Schottky barrier height. A smaller effective Schottky barrier height will lead to larger leakage current. Highlights: The leakage current characteristics can be a function of the bottom electrode of the MIM structure. The thickness of the bottom electrode affects the leakage current characteristics through two mechanisms. The thickness of the bottom W layer can affect Ta2 O5 layer CVD process. Rougher surface of the bottom W electrode can result in a smaller effective Schottky barrier height.